Structural Equation Modeling of the Relationships Between Intellectual Capital, Psychological Capital, and Human Resource Productivity - Robatmili, Morteza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The purpose of this study was to investigate the interrelationships among intellectual capital, psychological capital, and human resource productivity in the banking sector.Methods and Materials: The research employed a cross-sectional survey design using structural equation modeling (SEM). The statistical population consisted of managers of Parsian Bank branches in Tehran, from which 287 individuals were selected through simple random sampling. Data were collected using three instruments: Bontis’s Intellectual Capital Questionnaire, Luthans’s Psychological Capital Questionnaire, and a researcher-developed Human Resource Productivity Questionnaire. Reliability was confirmed with Cronbach’s alpha coefficients above acceptable thresholds, and validity was verified by expert review. Data analysis was performed using SPSS and LISREL, with model fit assessed through indices such as RMSEA, GFI, and AGFI.Findings: The results revealed that intellectual capital significantly and positively influenced human resource productivity. Among its components, human capital exerted the strongest effect (path coefficient = 0.37), followed by structural capital (0.29) and relational capital (0.23). In addition, psychological capital had a positive and significant impact on human resource productivity, with a standardized coefficient of 0.32. All path coefficients were statistically significant (t-values > 1.96), confirming the robustness of the relationships. Goodness-of-fit indices indicated that the proposed structural model adequately fit the data, with RMSEA = 0.077, GFI = 0.90, and AGFI = 0.89.Conclusion: The study underscores the dual importance of intellectual capital and psychological capital as complementary intangible resources that jointly enhance human resource productivity. By investing in knowledge-based assets and fostering positive psychological states among employees, organizations—particularly in knowledge-intensive industries like banking—can achieve sustainable improvements in productivity and competitiveness.